The Impact of the US-China Economy on the Economic Growth of OIC Member Countries - Fakhrunnas, Faaza; Fadillah, Abi (Global Review of Islamic Economics and Business, 2023)
As countries having sizeable economic scale, the US and China have significant contributions as well as influence on the world economy. Hence, the economic activities performed by both countries have a higher possibility to affect other countries’ economic conditions due to the presence of economic integration among the countries. The study aims to investigate the US-China economy impact which is proxied by a balance of trade (BOT), net foreign direct investment (FDI), and exchange rate (ER) on the economic growth of OIC member countries (EG). The study utilizes data from 1979-2018 and adopts Autoregressive Distributed Lag (ARDL) then applies a bounds testing approach to measure the short and long-run relationship between independent and dependent variables. The finding of the study shows that there is a long-run cointegration between the US-China economy impact on the economic growth of OIC member countries. The short-run ARDL model also indicates that all the independent variables have a significant relationship with the economic growth of OIC member countries across the regions. Originality/Value: The study comprehends as well as provides a new insight on the influence of the US and China's economic activities on OIC member countries’ economies.